2018
DOI: 10.1002/cam4.1620
|View full text |Cite
|
Sign up to set email alerts
|

Validation of multiple myeloma risk stratification indices in routine clinical practice: Analysis of data from the Czech Myeloma Group Registry of Monoclonal Gammopathies

Abstract: This study used data from the Czech Myeloma Group Registry of Monoclonal Gammopathies to validate the International Myeloma Working Group (IMWG) and revised International Staging System (R‐ISS) indices for risk stratification in patients with multiple myeloma (MM) in clinical practice. Patients were included if they had symptomatic MM, complete data allowing R‐ISS and IMWG staging (including cytogenetic information regarding t(4;14), t(14;16), and del(17p)), and key parameters for treatment evaluation. Median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…These results are similar to studies conducted by Radocha et al 11,19 Beta 2 microglobulin levels were high in patients with t(4;14) with mean ± SD of 7.07 ± 3.64 and in patients without t(4;14) it was 4.096 ± 2.064, (p=0.029) and these results were comparable with study conducted by Radocha et al 19,5 In positive patients the mean ± SD of S albumin was 38.38 ± 7.99 and in negative patients it was 37.74 ± 5.598, there was statistically insignificant difference between S albumin and t(4;14) (p=0.786). These results does not matched with results of Radocha et al 19,5 Most of the patients with t(4;14) presented with advanced stage according to ISS scoring.Whereas in t(4;14) negative patients 30% were in stage I, 37% in stage II, and 33% in stage III. These results were comparable with results of study conducted by Ja min byun in which according toISS, 54 patients (33.5%) were in stage I, 61 (37.9%) in stageII and 46 (28.6%) in stage III.…”
Section: Discussionsupporting
confidence: 93%
“…These results are similar to studies conducted by Radocha et al 11,19 Beta 2 microglobulin levels were high in patients with t(4;14) with mean ± SD of 7.07 ± 3.64 and in patients without t(4;14) it was 4.096 ± 2.064, (p=0.029) and these results were comparable with study conducted by Radocha et al 19,5 In positive patients the mean ± SD of S albumin was 38.38 ± 7.99 and in negative patients it was 37.74 ± 5.598, there was statistically insignificant difference between S albumin and t(4;14) (p=0.786). These results does not matched with results of Radocha et al 19,5 Most of the patients with t(4;14) presented with advanced stage according to ISS scoring.Whereas in t(4;14) negative patients 30% were in stage I, 37% in stage II, and 33% in stage III. These results were comparable with results of study conducted by Ja min byun in which according toISS, 54 patients (33.5%) were in stage I, 61 (37.9%) in stageII and 46 (28.6%) in stage III.…”
Section: Discussionsupporting
confidence: 93%
“…A Czech study recently conducted to validate the R-ISS and IMWG scores found that the majority of NDMM patients were DSS III (70.3%) and 26.7% DSS B [ 14 ]. Similarly, a Turkish study found that in patients older than 65 years, 21% were ISS I, 37% ISS II and 42% ISS III.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, data from the Czech Myeloma Group Registry of Monoclonal Gammopathies was used to validate the IMWG frailty score and Revised International Staging System (R-ISS) indices for risk stratification in patients with MM in clinical practice. The results concluded that the prognostic value of the IMWG and R-ISS risk stratification indices apply to patients with MM in real-world settings ( 41 ).…”
Section: Geriatric Assessment and Vulnerability Scoresmentioning
confidence: 92%